Rapid Kinetic Fluorogenic Quantification of Malondialdehyde in Ground Beef - Keshav Raj Bhandari; Max Wamsley; Bindu Nanduri; Willard E. Collier; Dongmao Zhang (Foods)
Malondialdehyde (MDA), a mutagenic and carcinogenic compound, is widely studied in the meat industry and lipid peroxidation research due to its implications for food quality and safety. Current methods for quantifying MDA in solid tissues are labor-intensive, requiring multiple instruments and approximately two hours to complete. This study presents an ultrafast kinetic fluorogenic method for quantifying MDA in ground beef, utilizing 2-thiobarbituric acid (TBA) as a fluorogenic probe. The total assay time is significantly shortened to 6 min from sample preparation to data acquisition. The assay’s robustness against matrix interference was validated using sample volume variation and standard addition calibration methods. Additionally, the effects of ambient exposure to air, washing, and cooking on MDA content in raw ground beef were quantified. While both ambient exposure to air and cooking increased MDA levels, washing raw ground beef and decanting cooked ground beef broth effectively reduced MDA levels in the ground beef. This simple and rapid assay can be adopted both in food research and industry. Moreover, insights from our study on the relationship between ground beef treatment and MDA concentration will help consumers make informed decisions about ground beef handling and consumption to lower their intake of MDA.